2020
DOI: 10.3390/foods9020171
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Mild Heating and Dielectric Barrier Discharge Plasma on the Reduction of Bacillus Cereus in Red Pepper Powder

Abstract: The synergistic efficacy of a combined treatment of mild heat (MH) and dielectric barrier discharge (DBD) plasma in Bacillus cereus-contaminated red pepper powder was tested. A cocktail of three strains of B. cereus (NCCP 10623, NCCP 14579, ATCC 11778) was inoculated onto red pepper powder and then treated with MH (60 • C for 5-20 min) and DBD plasma (5-20 min). Treatment with MH and DBD plasma alone for 5-20 min resulted in reductions of 0.23-1.43 and 0.12-0.96 log CFU/g, respectively. Combined treatment with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Next to heat treatment, further non-thermal technologies for the elimination/reduction of B. cereus spores in foods were established, with the aim of significantly reducing or inactiving spores without affecting the integrity and quality of the food, alone or in combination with mild heat treatment. These are pulsed light treatment [158], electron beam irradiation [159,160], continuous ohmic heating [161][162][163], dielectric barrier discharge plasma [164], acidic electrolyzed oxidizing (EO) water and slightly acidic EO water [140,165] coupled with ultrasonication [166,167], UV treatment [168,169], microwave-combined cold plasma treatment [170] and combined treatment with germinant compounds and superheated steam [171].…”
Section: Prevalence and Survival Of B Cereus In Foodsmentioning
confidence: 99%
“…Next to heat treatment, further non-thermal technologies for the elimination/reduction of B. cereus spores in foods were established, with the aim of significantly reducing or inactiving spores without affecting the integrity and quality of the food, alone or in combination with mild heat treatment. These are pulsed light treatment [158], electron beam irradiation [159,160], continuous ohmic heating [161][162][163], dielectric barrier discharge plasma [164], acidic electrolyzed oxidizing (EO) water and slightly acidic EO water [140,165] coupled with ultrasonication [166,167], UV treatment [168,169], microwave-combined cold plasma treatment [170] and combined treatment with germinant compounds and superheated steam [171].…”
Section: Prevalence and Survival Of B Cereus In Foodsmentioning
confidence: 99%
“…Additionally, if combined treatment achieves a synergistic effect, it can be considered a useful microbial decontamination technology. Jeon et al [ 45 ] reported that combined treatment with mild heat and DBD plasma to inactivate Bacillus cereus in red pepper powder resulted in a reduction of approximately 6 log CFU/g. The impact of DBD plasma on L. monocytogenes mixed-culture biofilms was assessed by quantifying the biofilms on stainless steel (SS) at various time intervals (5–60 min) following treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While research on flavourzyme, recognized as a natural antimicrobial agent, remains limited, our findings could alleviate concerns regarding alterations in food quality. As a non-thermal treatment method, cold plasma can exert negligible to minimal effects on the physical, chemical, nutritional, and sensory properties of many products [ 45 ]. However, interactions between RNS and ROS generated by plasma and food components can lead to carcinogenesis, destruction of essential nutrients, and alteration of protein, lipid, and carbohydrate functionalities [ 47 ].…”
Section: Discussionmentioning
confidence: 99%